Vulnerability in old age: definition and interventions in the field of Gerontology - Salmazo-Silva, Henrique (2013)
The aim of this paper is to discuss different aspects of vulnerability in old age and discuss the types of intervention that could be mobilized in the Gerontology field to prevent and minimize or delay the effect of vulnerability at the end of life. This study points to the fact that vulnerability in old age requires multifactorial actions and social responses in short, medium and long term, in order to help different cohorts of elderly.